The fast track land reform programme (FTLRP) and the youth in Umguza district, Matabeleland North: Zimbabwe - Nyamupingidza, Mandlenkosi Taurayi (My University, 2018)
The Fast Track Land reform Programme (FTLRP) in Zimabwe is a contentious issue particularly with regards to beneficiaries. However not much is understood about the impact of the FTLRP on the youth as literature has often failed to investigate the challenges that youth have in accessing land, particularly in Matabeleland North. This is troubling considering that Zimbabwe is a youthful country with a high unemployment rate. The research investigated whether the youth accessed land, the means they used and the livelihoods that they developed. The research was qualitative with Umguza District utilised as a case study. The data collection methods used were in-depth interviews and observation. The sample comprised of twenty individuals who were between 18-35 years during the FTLRP. Data collected from the interviewees and observation was analysed using Thematic Content Analysis. The findings of the study revealed that few young people in particular women accessed land with those that accessed land under-capacitated which led to under-utilisation of the land. Lack of resources negatively affected the livelihoods that the youth developed during and after the FTLRP. This means that the FTLRP has largely failed to be a vehicle outside traditional means that young people can access and utilise land for sustainable livelihoods.
A Research Report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for The Master of Arts Degree in Development Studies, Johannesburg, 2018
Keywords: Land reform--Zimbabwe; Land tenure--Zimbabwe; Zimbabwe--Economic conditions--21st century